Why it matters what people think: Beliefs, legal origins and the deep roots of trust - Fabian Wahl (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2012)
This paper analyses the connection between legal origins and generalized trust. Based on recent results of institutions and trust research it argues that legal origins and trust are connected via the beliefs of agents. Next, it develops hypotheses about a complex and self-reinforcing causal relation between both. It then shows empirically that indeed, legal origins and contemporary trust are robustly connected with each other. In a next step, it investigates the deep historical roots of trust to construct proxies for historical trust levels in 1500 AD. By making use of the historical trust scores and information about the exogenous or endogenous introduction of legal origins in certain countries it assess some of the claims about causality made before. Here, it found confirming evidence for the propositions of Aghion et al. (2010), namely that (i) countries for which legal origins are endogenous did develop other legal traditions depending on their ex-ante (historical) trust values and (ii) that the effects of an exogenous introduction of legal origins vary depending on ex-ante trust levels.
urn:nbn:de:bsz:100-opus-7419
Keywords: D02; K40; N10; O10; Z10; 330; Trust; Legal Origins; Colonization; Institutions; Causality; Deep Rooted Factors of Development